La utilización de los rincones de juego trabajo y su relación con el desarrollo cognitivo en los niños y niñas de primer grado de educación general básica de la escuela fiscal María Paulina Solís de la ciudad de Yantzaza, provincia de Zamora Chinchipe. Periodo lectivo 2013-2014. Lineamientos alternativos - Cuenca Velez, Mary Erlinda (2014)
This research work, entitled: "USING THE CORNERS OF GAME WORK AND ITS RELATIONSHIP WITH COGNITIVE DEVELOPMENT IN FIRST YEAR CHILDREN OF GENERAL BASIC EDUCATION FISCAL SCHOOL "PAULINE MARY SOLIS" OF Yantzaza CITY, ZAMORA CHINCHIPE province. SCHOOL YEAR 2013-2014 ". ALTERNATIVE GUIDELINES. It has been structured and developed in accordance with the Rules of the Academic Board of the National University of Loja. The overall objective was formulated; Check if corners of Game Work are related to the cognitive development in children at the First Year of General Basic Education. The methods used were the scientific, inductive, deductive, analytical, Synthetic, Descriptive and Statistical Model method; the techniques applied are the survey and test of Roldan Basic functions for data collection and processing framework. The survey of the Masterpieces preschool, to establish the use of Corners Play Working in the daily work, and Test of Basic Functions Roldan children First-Year Basic Education School Maria Paulina Solis to evaluate Cognitive Development. 100% of First Grade Teachers used ranging from pre Corners Play Working in the classroom twice a week. Using performing teachers is very short; they must make a daily one-hour session in order to take advantage of this alternative methodology that enables active participation of children in building their knowledge. In the corners containing time, space and resources that give it such a primordial as any other activity that takes place throughout the school day is planned category. 90 % of children in the First Degree variable presents itself with more than 50%, equivalent to Cognitive Development and 10% Satisfactory presents itself variable between 0 and 25 %, equivalent to an Unsatisfactory Cognitive Development. The 80 % variable presents no more than 50 %, equivalent to an Unsatisfactory Cognitive Development, 10% have no variable between 25 and 50 %, equivalent to an Unsatisfactory Cognitive Development, and 10% have no variable over 50 %, equivalent to an Unsatisfactory Cognitive Development. What is evident in the role of attention and fatigue only meet a girl achieving the outcome measure , therefore it must be allocated Corners Play Working with activities for the boy and girl have ability and skill pertaining to the care, participatory activities that encourage concentration, which are enriching , active to avoid fatigue in the teaching - learning.